Profile and Association between Self-Regulated Learning and Quality of Student Understanding in Mathematics Learning - Maghfiroh, Sasqia Ulimaz; Widjajanti, Djamilah Bondan (International journal of multicultural and multireligious understanding, 2025)
This study aims to describe the level of self-regulated learning for students with instrumental comprehension and relational comprehension and examine the association of comprehension quality with self-regulated learning of MTsN students in Banyuwangi Regency. This research is a survey research with quantitative approach. Sampling used proportional stratified random sampling. The sample size was 345 students from a population size of 2491. The instrument used was a self-regulated learning questionnaire. The validity used is content validation by experts and construct validity using Confirmatory Factor Analysis (CFA) while reliability uses Croncbach's alpha coefficient. All instruments were valid and reliable. Data analysis techniques used cross tabulation and Chi square test. The results showed that: (1) Students with instrumental understanding have a high level of self-regulated learning with an estimated proportion range between 46% and 71%. Students with relational understanding have a high level of self-regulated learning with an estimated proportion range between 47% to 74%, (2) There is a significant association between the quality of understanding and the level of self-regulated learning of students with a weak association strength using a significance level of 5%.